Validitas Pengetahuan Metafisik Analisis Konsep Kebenaran dalam Tafsir Sahl Al-Tustari: Penelitian - Khalim, Nor (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study responds to epistemological criticisms regarding the validity of esoteric exegesis (ishari), which is often viewed as subjective and detached from the authority of the revealed text. The primary objective of this study is to analyze the construction of ontological truth and the epistemological validity of metaphysical knowledge in Tafsir Sahl al-Tustari. Using a qualitative-library method with a philosophical-hermeneutic approach, this research examines the concepts of Al-Haqq, Haqiqa, and letter symbolism. The results indicate that Tustari defines truth not merely as logical correspondence, but as a living ontological reality. In-depth analysis reveals that the validity of this exegesis rests on the epistemology of Fahm (divine understanding), which requires a dialectical integration between tazkiyatun nafs (purification of the soul) and absolute obedience to Sharia. Furthermore, Tustari's metaphysics is proven to function as a systematic "spiritual science" through the mechanism of "Soteriological Semiotics," where symbols of letters and light are interpreted as ontological codes for salvation. This study concludes that Tustari's metaphysical knowledge possesses transformative validity that bridges rationality and spirituality, the verification of which is objectively measured through ethical transformation (akhlaq) and the certainty of faith (yaqin) of the interpreter.